Exploring the heat-induced structural changes of β-lactoglobulin -linoleic acid complex by fluorescence spectroscopy and molecular modeling techniques - Simion (Ciuciu), Ana-Maria (J Food Sci Technol, 2015)
Linoleic acid (LA) is the precursor of bioactive oxidized linoleic acid metabolites and arachidonic acid, therefore is essential for human growth and plays an important role in good health in general. Because of the low water solubility and sensitivity to oxidation, new ways of LA delivery without compromising the sensory attributes of the enriched products are to be identified. The major whey protein, β-lactoglobulin (β-Lg), is a natural carrier for hydrophobic molecules. The thermal induced changes of the β-Lg-LA complex were investigated in the temperature range from 25 to 85 °C using fluorescence spectroscopy techniques in combination with molecular modeling study and the results were compared with those obtained for β-Lg. Experimental results indicated that, regardless of LA binding, the polypeptide chain rearrangements at temperatures higher than 75 °C lead to higher exposure of hydrophobic residues causing the increase of fluorescence intensity. Phase diagram indicated an all or none transition between two conformations. The LA surface involved in the interaction with β-Lg was about 497 Ǻ(2), indicating a good affinity between those two components even at high temperatures. Results obtained in this study provide important details about heat-induced changes in the conformation of β-Lg-LA complex. The thermal treatment at high temperature does not affect the LA binding and carrier functions of β-Lg.